Engineered Bacillus subtilis WB600/ZD prevents Salmonella Infantis-induced intestinal inflammation and alters the colon microbiota in a mouse model - Wei Li; Xue Wang; Keyuan Chen; Yaohong Zhu; Guiyan Yang; Yipeng Jin; Jiufeng Wang (Veterinary Research)
Abstract Antimicrobial peptides (AMPs) are instrumental in maintaining intestinal homeostasis and have emerged as potential therapeutic candidates for ameliorating intestinal bacterial infections. However, the intrinsic instability associated with the in vivo delivery of AMPs constitutes a substantial impediment to their therapeutic efficacy in treating infections. In this study, we genetically modified Bacillus subtilis (B. subtilis) WB600 to express Zophobas atratus defensin (ZD), an antimicrobial peptide with broad-spectrum activity isolated from Zophobas atratus, for oral administration. This engineered strain effectively protects against Salmonella Infantis (S. Infantis) infection in mice. Pretreatment with WB600/ZD prevented NF-κB pathway activation induced by S. Infantis infection and increased expression of antioxidant and tight junction proteins, thus alleviating the severity of intestinal inflammation in both the jejunum and ileum (P < 0.01). Moreover, WB600/ZD pretreatment facilitated the growth of beneficial bacteria such as Lachnospiraceae, Butyricicoccus, Eubacterium_xylanophilum, and Clostridia_UCG-014 while decreasing the abundance of pathogenic bacteria such as Escherichia-Shigella and Salmonella (P < 0.05). In conclusion, this study underscores the protective effects of WB600/ZD on S. Infantis-induced intestinal inflammation, suggesting that oral delivery of B. subtilis WB600/ZD may be a promising prophylactic strategy for combating bacterial infections in the intestine.